2009
DOI: 10.1021/ef8005838
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Stability of Sorbents Removing H2S from Hot Coal Gas

Abstract: Mixed metal oxide containing iron with the high-sulfur capacity and reactivity is considered as one of the most favorable sorbents for desulfurization in hot gas. The stability and life of iron-based sorbents are the main challenges for the hot gas cleanup techniques. Not only the effect of gas atmosphere but also the effect of ZnO and MgO on the stability of iron-based sorbent was studied in this work. The mechanism and factors influencing sorbent stability are discussed. The results showed that the coexisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Based on this, there were many investigations of single metal oxide and mixed metal oxides as sorbents in the past [7][8][9][10][11]. And iron oxide has become the study focus for advantages of low cost, high sulfurization rate, good regeneration ability and superior sulfur capacity [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, there were many investigations of single metal oxide and mixed metal oxides as sorbents in the past [7][8][9][10][11]. And iron oxide has become the study focus for advantages of low cost, high sulfurization rate, good regeneration ability and superior sulfur capacity [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…(10), the formation of COS is preferred when the system has plenty of CO but is absent from H 2 . However, since the COS peaks appear only after 0.7 min min À1 , metal Fe may need to be presented as a catalyst for the gas reaction after the time needed for the reduction of Fe 2 O 3 through Fe 3 O 4 and FeO to Fe (Chang et al, 2009) or the reduction of FeS to Fe according to Eqs. (7) and (12).…”
Section: Effect Of Carbon Monoxidementioning
confidence: 99%
“…However, a new species, CH 4 , is also produced in this combined CO and H 2 system which is different from that of the CO only system. This may happen when Fe 2 O 3 is reduced further to Fe and a part of CO is reduced by H 2 to C after the breakthrough of H 2 S (Zhao et al, 2002;Chang et al, 2009). The reaction can be shown as Eq.…”
Section: Combined-effects Of Co and Hmentioning
confidence: 99%
“…To be environment-benign and to avoid corrosion of downstream equipments, H 2 S in hot coal gas has to be removed prior to syngas utilization [2,3]. Recent studies indicated that oxides of Fe, Zn, Cu, Mn and Co are good sorbents for such a goal [4][5][6][7][8]. However, the utilization of sorbent materials is limited because specific surface area and pore volume are low.…”
Section: Introductionmentioning
confidence: 99%